Alternative Views on the Link between Risk Aversion and Diminishing Marginal Utility of Wealth - Vojtěch Menzl (European Financial and Accounting Journal, 2021)
Although the link between risk aversion and diminishing marginal utility of wealth is academically well established, theoretical discussions concerning its empirical validity remain. The presented, review-type paper aims to briefly examine theoretical roots responsible for the different views on this association in order to provide a broader perspective to alternative explanations. This latter task is assisted by comparative analysis of two recent pieces of research by Rick Falkenstein and Matthew Rabin; a duo of papers, handpicked at the author's discretion to demonstrate the convergence of alternative ideas from different authors (and backgrounds). In support of its argumentation, the paper also presents a critical overview of the equity premium puzzle as seen through the prism of behavioural finance. The main contributions of the paper include evidence-based support for the concept of relative utility and reconfirmation of the meaningful role of behavioural finance in economics and finance.
Keywords: D81; G11; G12; 650; Risk Aversion; Marginal Utility; Expected Utility; Behavioural Finance; Equity Premium Puzzle